Geography and education: music as methodology in Geography Teaching/Geografia e educação: a música como metodologia no ensino da Geografia - Soraya Oliveira Gonzaga; Klévia Lima Delmiro; Claudionor de Oliveira Silva (Universidade Estadual de Alagoas, 2020)
The objective is to demonstrate how music contributes to create learning strategies for curriculum components, especially geography to culminate in integral and meaningful learning. This work has a qualitative character, being carried out from literature review, exploratory technical visit in the space lived during Supervised Internship IV and experience report. Therefore, the use of music as a work tool allows teachers to systematize their educational practice by applying methodology that contemplates these guidelines, composing their plans and lesson plans in the form of "music to sing", "music to play", "music to dance "or" music to perform "depending on the content worked and the degree of understanding of the students, and the presentation of songs as a suggestion for application in the classroom, so that the students' response is the understanding of reality, their role social and political issues in society for the exercise of citizenship.